ABC7-Konsens zur Systemtherapie des fortgeschrittenen Mammakarzinoms - Lüftner, Diana; Ditsch, Nina; Fasching, Peter; Busch, Steffi; Ettl, Johannes; Haidinger, Renate; Jackisch, Christian; Müller, Lothar; Müller, Volkmar; Ruckhäberle, Eugen; Schumacher-Wulf, Eva; Thomssen, Christoph; et al. (Die Onkologie, 2024)
Background: The 7th “International Consensus Conference on Advanced Breast Cancer” (ABC) met from 9–12 November 2023 in Lisbon, Portugal. The consensus is organized by a group of experts from different countries and disciplines. Rationale: The rationale of the international consensus conference is to standardize the treatment of patients with primarily inoperable, locally advanced or with metastatic breast cancer worldwide on an evidence-based basis and to ensure that adequate therapy is possible in all countries. This manuscript discusses the on-site voting results of the ABC7 panel for everyday clinical practice in Germany. Basis: The discussion is related to the German guidelines of the “Arbeitsgemeinschaft Gynäkologische Onkologie” (AGO Organkommission Mamma, Version 2024.1D) which is updated annually, most recently in March 2024. Results: In this manuscript, the focus is on systemic treatment of patients with metastatic cancer. Special topics included the treatment of patients with oligometastases, leptomeningeal disease, and brain metastases and of pregnant patients. As in previous years, patient representatives from all over the world took part in the conference and were involved in reaching consensus.
CRIS-Team Scopus Importer:2024-10-25
Keywords: ABC and pregnancy; ADCs; Brain metastases; Leptomeningeal disease; Oligometastases